STUDI PEMBUATAN BROWNIES KUKUS DENGAN SUBSTITUSI TEPUNG DAUN SINGKONG (MANNIHOT UTILISSIMA): (The Making Of Brownies Substituted with Cassava (Mannihot utilissima) Leaf Flour) - Zainal Zainal; Amran Laga; Rahmatiah Rahmatiah (Hasanuddin University Food Science and Technology Study Program, 2018)
Cassava leaves are abundant green leaves and affordable. This research uses cassava leaves of sleedlings type with white, pink stalk with light green leaf colour made into flour to be processed food products. The purpose of this research was to analyze the physical properties and chemical content of brownies steamed by the addition of cassava leaf flour based on a mineral test (Ca, P, Fe), water content, ash content, protein content, fat content, carbohydrate and crude fibre content. A panellist assessment of brownies steamed based on organoleptic test results and determining the formulation of good brownies cake products from the ratio of wheat flour and cassava flour used. This research was designed using Completely Randomized Design (RAL) with three replications such as A0 (100% wheat flour: 0 (control)), A1 (85% wheat flour: 15% cassava flour), A2 (70% wheat flour: 30% cassava flour) and A3 (55% wheat flour: 45% cassava flour). The parameters observed were proximate tests which included (water content, ash content, protein content, fat content, carbohydrate content), mineral tests (Ca, P, Fe), crude fibrecontent, organoleptic test. The best treatment was A3 which has water content 20,83%, ash content 2,88%, protein content 9,48%, fat content 23,68%, carbohydrate 42,13% and fiber content 1,12%, content mineral calcium 12.56 g / kg, phosphorus 2.06 g / kg, iron 61.06 ppm. The result of the panellist's assessment of the level of preference to steamed brownies was A0 with the average value of organoleptic score is texture 4.08 (like), colour 4,1 (like), taste 4.04 (like), and flavour 4 (like)